A Classification of Separation Methods. Issue 1 (2nd January 2016) - Moskvin, Leonid N.
Abstract : A general classification of separation methods is attempted. The two criteria were phase transformations and interfacial transfers. All separation methods of homogenous mixtures were divided into five groups: (i) methods that are based on the formation of new phases by substances to be separated; (ii) methods that are based on differences in the interphase distribution processes, chromatographic methods being singled out as a separate group; (iii) membrane methods that are based on induced transfers of substances from one phase into another one across a third phase, which separates the two; (iv) separation methods within a single phase that are based on velocity and direction differences in spatial displacement of particles of substances to be separated within one fluid phase under the action of various fields; and (v) combined methods working combining previously listed methods. Descriptions of each group of separation methods include their intragroup classification and information on the most important techniques as well as the least known of them. These descriptions are in the form of reviews of fundamental and most important publications, regardless of the time they appeared. For the well-known classical methods of the first group all necessary information can be found in university textbooks.